Pre-Formulation Study on The Preparation of Skin Cosmetics - Ahmad Ainurofiq; Anita Maharani; Fitri Fatonah; Hainun Nisa Halida; Tejayani Nurrodlotiningtyas (Science and Technology Indonesia, 2021)
Cosmetics have been a trend necessary for all people. The increasing need of the community in the use of cosmetics becomes the basis of the formulation of this article. Pre-formulation study for cosmetics is important to ensure that the final preparation of the cosmetics is safe to use and has maintained quality. A pre-formulation study for cosmetics is a study of physicochemical characteristics associated with the substances used in the formulation of cosmetics preparation to produce a quality cosmetic product. The pre-formulation study described here includes evaluation of sensitivity and irritability, organoleptic, formulation compatibility, thermal effect, partition coefficient, stability, particle size, wettability, hygroscopicity, type of preparation, and pH. This review article is compiled by searching for literature associated with the topic studied. Taken together, this review suggests that the pre-formulation study described recommended to be performed during the information searching step related to the physicochemical properties of ingredients used for cosmetic preparations. All of the topic studied is beneficial to determine the quality of the ingredients within the preparation before formulation, therefore, the production of cosmetic preparation can be more effective because it directs the choice of ingredients and optimum ingredient composition.